Tinjauan Hukum Terhadap Keabsahan Pengalihan Hak Atas Saham dari Harta Bersama - Ngadiman, Sidik Nur; Nugroho, Meysita Arrum (PT Elaborium Elevasi Indonesia, 2025)
This abstract discusses the legal review of the validity of the transfer of rights to shares of joint property in the context of applicable laws and regulations. The transfer of shares in joint property can raise various legal issues related to the separation or division of property in a marriage. Joint property, which consists of goods acquired during marriage, has a special legal status, and any change in ownership status, including the transfer of shares, must be carried out by considering the principles of justice and balance of rights between husband and wife. In practice, the transfer of shares carried out without mutual consent or without proper legal procedures can risk causing disputes between the parties involved. Therefore, it is important to understand the legal basis governing the transfer of shares of joint property, including the rights and obligations of each party involved in the agreement. In addition, the regulation regarding the transfer of rights to shares of joint property also needs to refer to the provisions regarding the division of property in divorce or separation, where each party is entitled to obtain a fair share of the results of the joint business. A valid transfer of shares must follow the procedures established by law in order to avoid actions that are detrimental to one of the parties. Understanding the legal aspects of share transfer is very important to maintain the validity of the transaction and avoid potential legal disputes in the future.